2017
DOI: 10.1371/journal.pone.0187979
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of filamentous actin probe expression in neuronal cells

Abstract: Genetically encoded filamentous actin probes, Lifeact, Utrophin and F-tractin, are used as tools to label the actin cytoskeleton. Recent evidence in several different cell types indicates that these probes can cause changes in filamentous actin dynamics, altering cell morphology and function. Although these probes are commonly used to visualise actin dynamics in neurons, their effects on axonal and dendritic morphology has not been systematically characterised. In this study, we quantitatively analysed the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
(77 reference statements)
3
14
0
Order By: Relevance
“…Our findings are more strongly marked in undifferentiated human stem cells, which may be due to a higher capacity to uptake the adenovirally-delivered Lifeact plasmid. Nevertheless, we obtain similar dose-response trends in immortalized cell lines (NIH/3T3 and COS-7), thus expanding the range of cells types were Lifeact has been shown to induce aberrant morphologies 8,9,24 . It is worth stressing that, in our hands, Lifeact affects different cells types to a different degree, and some cytoskeletal features more strongly than others.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Our findings are more strongly marked in undifferentiated human stem cells, which may be due to a higher capacity to uptake the adenovirally-delivered Lifeact plasmid. Nevertheless, we obtain similar dose-response trends in immortalized cell lines (NIH/3T3 and COS-7), thus expanding the range of cells types were Lifeact has been shown to induce aberrant morphologies 8,9,24 . It is worth stressing that, in our hands, Lifeact affects different cells types to a different degree, and some cytoskeletal features more strongly than others.…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, we note that the dose-response trends are typically preserved between cell types, thus suggesting a common origin of the observed changes. The Lifeact plasmid we used included a CMV promoter, which has been shown by others to induce milder aberrations than pBABE and CAG 8 . Of note, our results using a recombinant Lifeact-TagGFP2 protein show that the effect of Lifeact is similar regardless of the way in which the DNA (or protein) is delivered and expressed into the cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to submembrane actin assemblies, a few electron microscopy studies had reported the presence of deeper intra-axonal actin filaments interspersed among microtubules (Bearer and Reese, 1999;Fath and Lasek, 1988;Nagele et al, 1988). Using a GFP-tagged calponin-homology domain of utrophina non-perturbing, high fidelity probe for filamentous actin (Burkel, 2007;Melak et al, 2017;Patel et al, 2017) -Ganguly et al observed the dynamics of actin along axons (Ganguly et al, 2015). Beyond the random bidirectional movement previously described (Chetta et al, 2015), they identified two new actin structures: static clusters of actin every 3-4 μm along axon shafts that appear and disappear within minutes called actin hotspots, and filaments up to 10 μm in length that grow in both directions at~1 μm/ s, called actin trails (Ganguly et al, 2015) (Fig.…”
Section: Hotspots and Trailsmentioning
confidence: 99%